Case report for human infection with a highly pathogenic avian influenza A(H5N6) virus in Beijing, China 2019 - Lei Yang; Xiang Zhao; Xiyan Li; Hong Bo; Duo Li; Jia Liu; Dayan Wang (Elsevier, 2020)
Bird infections with highly pathogenic avian influenza A(H5N6) viruses have been identified since 2014. With very limited occasion, the virus could sporadically spilled over to infect humans. It has been recognized that all human infections were within southern region of Mainland China until the case reported here in Beijing in Aug. 2019. This was the first human case infected with highly pathogenic avian influenza A(H5N6) virus in northern China. The infection was confirmed by real-time RT-PCR assay. The whole genome sequences were obtained from clinical sample. Genetic characteristics of the virus were identified similar to those of previous avian influenza A(H5N6) viruses, retaining the main features of the avian influenza virus.